Established methods and new opportunities for pore water stable isotope analysis. Issue 25 (20th September 2015) - Sprenger, Matthias; Herbstritt, Barbara; Weiler, Markus
Abstract: The vadose zone plays a crucial role in the water cycle for storing water, providing water to vegetation and transporting solutes or degrading contaminants. Earth scientists have long acknowledged the importance of the vadose zone, and numerous methods have been developed to better understand and predict hydrological processes within this 'critical zone'. For several decades, stable isotopes ( 18 O and 2 H) of pore water have been used as environmental tracers to gain insights into vadose zone water movement and other processes. To determine the pore water stable isotopic composition, various sampling procedures have been developed. We present the procedure and the accompanied advantages and drawbacks of each method. We further discuss possible opportunities and limitations regarding the scale of interest and the pore space that is sampled. The methodological review reveals that the choice of sampling method is crucial for the interpretation of pore water stable isotopes in the vadose zone, but a thorough comparison between the different methods is yet missing. Spiking experiments, where water of known isotopic composition is added to oven‐dried soil, have been shown to be questionable, as the extracted water is usually depleted compared with the standard water. A comparative study analysing soil samples with the recently developed direct water vapour equilibration method and the widely used cryogenic extraction shows deviations, which can only be partly explained, but discloses the need for a more thorough experimental comparative study. Especially promising are developments of continuous isotope measurements based on laser‐based spectrometry that will open up new opportunities for analysing pore water isotopes with higher temporal and spatial resolutions, revealing new insights into hydrological processes across various temporal and spatial scales. Copyright © 2015 John Wiley & Sons, Ltd.